Constitutional Remedies for Enforcement of Fundamental Rights in Ethiopia and India: A Comparative Study - Afesha, Nigussie; Barrett, Hazel Rose (Nordic journal of human rights, 2025)
Incorporating constitutional remedies is vital for effective and successful implementation of fundamental rights enshrined in a constitution. Variation exists among modern states with respect to constitutional remedies to protect fundamental rights against state actions. The mere incorporation of fundamental rights could be hollow unless they are buoyed and reinforced by effective enforcement mechanisms. Including constitutional remedies in a constitution plays an important role in preserving and defending fundamental rights. This paper examines the status and content of constitutional remedies in the Indian and Ethiopian constitutions in terms of their implications for the enforcement of fundamental rights. This study reveals that the Indian Constitution provides constitutional remedies and allows citizens to move directly to the Supreme Court to enforce their fundamental rights. By contrast, the Ethiopian Constitution not only suffers from a lack of constitutional remedies but also inhibits courts from reviewing legislation, executive actions, and administrative decisions that infringe fundamental rights. We conclude that constitutional and legislative measures to ensure the peaceful enjoyment of fundamental rights are an essential element of any federal system.